Anomalous self-experiences are strongly associated with negative symptoms in a clinical high-risk for psychosis sample - Tor Gunnar Værnes (Comprehensive Psychiatry, 2019)
Objective: Anomalous self-experiences (ASE) are considered as central features of the schizophrenia spectrum disorders and prodromal schizophrenia. We investigated total and single-item prevalence of these phenomena in a clinical high-risk (CHR) for psychosis sample, and associations with conventional psychosis-risk symptoms, present and childhood global/psychosocial functioning, and childhood trauma. Methods: The sample (n = 38) included 31 CHR, according to ultra-high risk or cognitive basic symptoms (COGDIS) criteria, and seven with non-progressive attenuated positive symptoms. Psychopathological evaluations included the Examination of Anomalous Self-Experience (EASE), Structured Clinical Interview for Prodromal Syndromes (SIPS), Schizophrenia Proneness Instrument – Adult (SPI-A) (only the COGDIS-criteria), a diagnostic interview (SCID-I), Global Assessment of Functioning – Split version (S-GAF), Premorbid Adjustment Scale (PAS) and Childhood Trauma Questionnaire (CTQ). Results: The mean total EASE score was in line with reports from other CHR samples, and was particularly enhanced in schizotypal personality disorder and in subjects fulfilling COGDIS-criteria. The four most frequent EASE-items were present in two-thirds or more of the participants. EASE total was significantly associated with negative and disorganization symptoms. A multiple regression analysis revealed that the level of negative symptoms explained most of the variance in EASE total. Conclusions: These results corroborates other findings that anomalous self-experiences are frequent and important features in CHR conditions and in the schizophrenia spectrum. The strong associations with negative symptoms and cognitive disturbances (COGDIS) should be investigated in longitudinal studies to address causality, psychopathological pathways and schizophrenia spectrum specificity. The weaker correlation between EASE total and positive symptoms may partly be related to a restricted range of positive symptoms. Keywords: Basic self-disturbance, anomalous self-experiences, clinical high-risk for psychosis, schizophrenia spectrum disorders, negative symptoms, cognitive disturbances